Памятники ямной культуры в нижней части Рэута в лесостепной Молдове - Попович, С.С. (Материалы по археологии Северного Причерноморья, 2015)
This article provides a brief description of barrow fields of Yamnaya culture situated on the lower part of middle Rгut river. Tribes of Late Yamnaya culture probably survived until the appearance of the Multi-cordoned ware (Mnogovalikovaja/Babyno) culture on this territory. It is possible that these tribes rendered armed resistance to the representatives of Katacomb culture. That’s why the absence of graves of Katacomb culture in this microregion fulfilled with Late Yamnaya culture burial grounds is not occasional one. On the other hand, big number of the graves of Late Yamnaya culture are stratigraphically replaced with burials of Multi-cordoned ware culture. Probably the reason of a such long stay of Late Yamnaya culture on this territory was in favorable opportunities for cattle breeding and seasonal agriculture.